Experiences of Egyptian Female Journalists With Workplace Gender Discrimination - Ismail, Mai (AUC Knowledge Fountain, 2019)
There is an upward trend in the employment of women in the media worldwide and in the Middle East. Despite their growing presence, women working in the industry continue to experience discrimination, gendered practices and sexist attitudes at the workplaces. This study examines the experiences of Egyptian women journalists. It employs a qualitative approach, building on in-depth interviews conducted with twenty early- to mid-career Egyptian female journalists. These work in state-run, private and independent news organizations whether in print, broadcast or online media. The analysis shows that the experience of female journalists is linked to various factors pertaining to the media environment; the ownership structure of media outlets; and the existence of sexist workplace cultures. Interviews show that women working in private organizations often face the most severe experiences of gender discrimination due to lack of job security and compromised working conditions. Interviewed women working in organizations with independent funding reported less severe experiences. Interviewed women note that they face discrimination in five main areas: discriminatory hiring promotion and wage policies; difficulty maintaining work-life balance; sexist workplace practices and sexual harassment; discrimination in the allocation of important reporting assignments and contentious relationships with leaders including women leaders.